Effect of Market Information on Student’s Investment Behavior - Gupta, Prakash; Upadhyay, Basudev (Nepalese Journal of Business and Management Studies, 2022)
The study focuses on analyzing the effect of market information on students’ investment behavior in the stock market by employing a sample size of 103 TU BBA students in Sorahkhutte. The data were collected using a structured questionnaire containing yes/no responses, multiple-choice questions, ranking questions, and Likert scale questions measured in different scales. The survey was conducted in the month of November 2021. One of the factors influencing investing behavior is market information. The research design embraced in the study were descriptive, relational, and causal research designs. Various tools used for data analysis were mean, median, standard deviation, Independent sample t-test, correlation, regression, etc. The study’s findings revealed that market information significantly affects students’ investment behavior in the Nepali stock market. The study will guide students and other investors to improve, exercise, and promote their investing strategy, planning, and procedures.